Strong-field spectral interferometry using the carrier-envelope phase - Ott, Christian; Schönwald, Michael; Raith, Philipp Nils; Kaldun, Andreas; Sansone, Giuseppe; Krüger, M.; Hommelhoff, P.; Patil, Y.; Zhang, Y.; Meyer, Kristina; Laux, Martin; Pfeifer, Thomas (New journal of physics, 2013)
The carrier-envelope phase (CEP) of ultrashort laser pulses is an important parameter in strong-field physics that controls temporally localized events on a sub-cycle timescale. The relative timing of these events is directly encoded into the measured spectral intensity distribution, and can be accessed by the use of spectral interferometry. Here, we combine this analysis with CEP control in a two-dimensional way, creating a novel spectroscopic method to explore the temporal dynamics of strong-field processes. We apply this general method to CEP-dependent high-harmonic generation and find that contributions of three different sub-cycle electron quantum paths can be separated, allowing one to quantify the dipole-phase dependence on the CEP in the non-adiabatic regime. The CEP-dependent time delay between two full-cycle spaced attosecond pulses was determined to modulate by 54 ± 16 as. We confirm the generality of the method by further applying it to CEP-dependent photoemission from a nanoscale metal tip.